Optimum Condition for Asparginase Activity in Crude Extract of Capiscum annum - Suhail Zbar, Nedhaal (Iraqi Journal of Science, 2023)
In this study asparaginase was extracted from fruit part of Capiscum annum then Asparaginase activity was detected and optimised. Optimum conditions for the activity of crude asparaginase were studied. Results showed maximum activity of asparaginase was achieved 140 u/ml when the enzyme was incubated with 200 mM of asparagines at 35 °C for 30 minutes in the presence of 0.05 M of potassium phosphate buffer solution at pH 8.